1998
DOI: 10.2139/ssrn.1815994
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Arrangements and Fiscal Performance: The Latin American Experience

Abstract: As we shall see later, in addition to income per capita, the degree of openness of an economy to international trade, the degree of indebtedness, and the age distribution of the population are other important determinants of the size of government. 4. We report here the median rather than the average due to the existence of outliers in Latin America, such as Nicaragua and Guyana, two small countries that are very highly indebted. For the OECD countries, the median and the mean are virtually the same. The avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 30 publications
3
42
0
Order By: Relevance
“…32 An additional channel that may explain differences in procyclicality across countries is that, for a given variability of the tax base, countries may differ in the intensity of the political pressures for additional spending that they face in good times, as reflected in a bsteeperQ slope of the f-function. Based on a sample of 26 Latin American countries, Stein et al (1999) find evidence that, after controlling for the volatility of the tax base, a higher level of political fragmentation leads to a more procyclical response of government spending. Such finding would be consistent with models in which a larger degree of political polarization and instability leads to a more inefficient tax system, as in Cukierman et al (1992).…”
Section: Interpreting the Evidencementioning
confidence: 99%
“…32 An additional channel that may explain differences in procyclicality across countries is that, for a given variability of the tax base, countries may differ in the intensity of the political pressures for additional spending that they face in good times, as reflected in a bsteeperQ slope of the f-function. Based on a sample of 26 Latin American countries, Stein et al (1999) find evidence that, after controlling for the volatility of the tax base, a higher level of political fragmentation leads to a more procyclical response of government spending. Such finding would be consistent with models in which a larger degree of political polarization and instability leads to a more inefficient tax system, as in Cukierman et al (1992).…”
Section: Interpreting the Evidencementioning
confidence: 99%
“…Finally, ethno-linguistic diversity is just one indicator of political fragmentation though undoubtedly a widely available and clearly exogenous one. To check for robustness, we used two alternative measures of political fragmentation examined earlier by Stein et al (1999). These measures are the bnumber of effective partiesQ (EFEC) and the logarithm of bdistrict magnitudeQ (LDM).…”
Section: Growth Regressionsmentioning
confidence: 99%
“…The latter measures the average number of representatives elected per district. Stein et al (1999) showed that for Latin American countries, higher values of either variable are associated with larger governments, larger deficits, and a more procyclical response to the business cycle. 19 The variables are however available only for OECD and Latin American countries and that too for the period 1991-1995.…”
Section: Growth Regressionsmentioning
confidence: 99%
“…These works include those of Von Hagen (1992) and Von Hagen and Harden (1994), for EU countries, Alt and Lowry (1994) for the U.S. states, Alesina et al (1999), Filc and Scartascini (2004) and Stein et al (1988), for Latin America, Gleich (2003) for eastern European countries and Dabla-Norris et al (2010) for low-and middle-income countries.…”
Section: Budget Institutionsmentioning
confidence: 99%